The Principal's Role in Implementing Merdeka Curriculum in Elementary Schools: Peran Kepala Sekolah dalam Implementasi Kurikulum Merdeka di Sekolah Dasar - Winarto, Rian Hadi; Rindaningsih, Ida (Universitas Muhammadiyah Sidoarjo, 2025)
General background: The Independent Curriculum provides educators and students with the freedom to design learning according to contextual needs. Specific background: SDN Gunungsari II has implemented the Independent Curriculum in alignment with its principles for an extended period. Knowledge gap: However, limited studies specifically explore the comprehensive role of school principals in leading its implementation within elementary education, particularly in rural contexts. Aims: This study aims to describe the principal’s roles, identify supporting and inhibiting factors, and outline the principal’s strategies in implementing the curriculum at SDN Gunungsari II. Results: Findings reveal that the principal plays essential roles as educator, manager, administrator, supervisor, leader, innovator, and motivator, with significant influence on program continuity. Key challenges include limited teacher understanding, insufficient facilities, and inconsistent government policies, while supporting factors include teacher competency development, active participation in curriculum design, and provision of locally relevant learning materials. Novelty: This study provides a detailed, role-based framework for principal leadership in curriculum implementation. Implications: The findings offer practical insights for policymakers and school leaders in optimizing curriculum application in elementary schools. Highlights: Comprehensive mapping of principal’s roles in curriculum implementation Identification of specific supports and barriers in rural school settings Practical leadership framework for elementary school principals Keywords: Kurikulum Merdeka, School Principal Role, Leadership, Elementary Education, Implementation Strategy